PENGEMBANGAN BAHAN AJAR DIGITAL BERBASIS POWERPOINT KOMBINASI ANIMASI DAN VIDEO PEMBELAJARAN MATERI ROTASI DAN REVOLUSI BUMI UNTUK SISWA KELAS VI - Tri Darsih; Irwan Koto; Endang Widi Winarni (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2022)
AbstractThe objectives of this study are (1) to produce digital teaching materials using PowerPoint with a combination of learning videos on the earth's rotation and revolution (2) to measure the feasibility of digital teaching materials using PowerPoint on earth's rotation and revolution (3) To describe the response of teachers and students of class VI to the use of digital teaching materials in online science learning. This development research referred to the stages of research and development of the ADDIE model consisting of four development procedures, which include: (a) the analysis phase, (b) the design phase, (c) the development phase, and (d) the implementation phase. However, this study only implemented three stages since students learned from home. The subjects in this study were sixth-grade students of the public elementary school in Kaur district, with eight males and 14 females. This research produces a product in the form of teaching materials in PowerPoint combined with learning videos in the form of files and links uploaded on YouTube. Based on the validation of the three aspects, digital learning material was valid (feasible), and the sixth-grade students could use it in learning. Six validators in their fields validated the product.